2010
DOI: 10.3350/kjhep.2010.16.1.49
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between hepatitis B virus infection and the incidence of pancreatic cancer: a retrospective case-control study

Abstract: There was no significant association between seropositivity for HBsAg or anti-HCV and PC. Further studies are warranted to clarify the association between HBV infection and PC in regions where HBV is endemic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 29 publications
0
11
1
Order By: Relevance
“…After review, two studies were excluded with the following reasons: a study of HCV infection (El-Serag et al, 2009); a case report (Yoo et al, 2009). Thus, eight articles met the inclusion criteria (de Gonzalez et al, 2008;Hassan et al, 2008;Gordon et al, 2009;Iloeje et al, 2009;Hong et al, 2010;Zhu et al, 2011;Ben et al, 2012;Wang et al, 2012), six of these studies were conducted only in East Asia (de Gonzalez et al, 2008;Iloeje et al, 2009;Hong et al, 2010;Zhu et al, 2011;Ben et al, 2012;Wang et al, 2012) and two in USA (Hassan et al, 2008;Gordon et al, 2009).…”
Section: Literature Search and Studies Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…After review, two studies were excluded with the following reasons: a study of HCV infection (El-Serag et al, 2009); a case report (Yoo et al, 2009). Thus, eight articles met the inclusion criteria (de Gonzalez et al, 2008;Hassan et al, 2008;Gordon et al, 2009;Iloeje et al, 2009;Hong et al, 2010;Zhu et al, 2011;Ben et al, 2012;Wang et al, 2012), six of these studies were conducted only in East Asia (de Gonzalez et al, 2008;Iloeje et al, 2009;Hong et al, 2010;Zhu et al, 2011;Ben et al, 2012;Wang et al, 2012) and two in USA (Hassan et al, 2008;Gordon et al, 2009).…”
Section: Literature Search and Studies Characteristicsmentioning
confidence: 99%
“…In most of the studies (de Gonzalez et al, 2008;Hassan et al, 2008;Gordon et al, 2009;Zhu et al, 2011;Ben et al, 2012;Wang et al, 2012), pancreatic cancer was diagnosed according the histology. In other studies (Iloeje et al, 2009;Hong et al, 2010), pancreatic cancer is confirmed by histology or diagnosed by symptoms, signs and more than two types of imaging tools. Enzyme-linked immunosorbent assay was used to test the presence of HBsAg and hepatitis B core antigen antibody (anti-HBc), hepatitis B e antigen (HBeAg) and hepatitis B e antibody (anti-HBe).…”
Section: Literature Search and Studies Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations